Grandparents of children with cancer: Quality of life, medication and hospitalizations. Issue 1 (21st July 2016) - Wakefield, C. E.; Fardell, J. E.; Doolan, E. L.; Drew, D.; De Abreu Lourenco, R.; Young, A. L.; Cohn, R. J.
Abstract: Background: Grandparents can play a crucial role of providing emotional and practical support for families facing childhood cancer. Yet, many have their own healthcare needs. This controlled study systematically assesses the impact of childhood cancer on grandparents' quality of life (QOL). Our objective was to compare QOL in grandparents of children with and without cancer and to identify factors associated with grandparents' QOL. Procedure: Grandparents (N = 222) completed two patient‐reported outcome (PRO) measures assessing QOL: EQ‐5D‐5L and WHOQOL‐BREF . Secondary endpoints included sleep, medications and hospitalizations. We used independent samples t ‐tests and multivariate linear regression to assess between‐group differences and identify predictors. Results: Grandparents of children with cancer (n = 89) reported significantly worse QOL than controls (n = 133) [mean WHOQOL‐BREF score: 75.6 (SD = 17.6) vs. 81.5 (15.6), P  = 0.007; mean EQ‐5D‐5L index value: 0.777 (0.20) vs. 0.874 (0.14), P  < 0.001)]. They also reported more problems with anxiety and depression (47.2 vs. 21.8%, P  < 0.001) and pain (64.8 vs. 49.6%, P  = 0.031). Grandparents of children with cancer reported taking longer to fall asleep [mean: 30.4 min (55.6) vs. 18.2 (20.2), P  = 0.011] and taking more medications in the last 4 weeks [mean: 2.9 (SD = 3.8) vs. 1.8 (SD = 2.3), P  = 0.012]. Hospitalizations were comparable across groups. Grandmothers, those living in urban locations, and retired/unemployed grandparents experienced reduced QOL. Conclusions: Grandparents are significantly affected by childhood cancer. The impact appears across many domains of life and results in meaningful QOL differences. Given that four or more individuals may be affected per child, and that grandparent well‐being can influence the whole family, interventions targeting at‐risk grandparents are needed.